Synchronous Integration Method of System and Simulation Models for Mechatronic Systems Based on SysML - Changyong Chu; Chengfang Yin; Shaohui Su; Chang Chen (Machines, 2022)
System architecture could be described clearly and unambiguously by a descriptive system model during the system-level design of mechatronic products. However, for system verification, it is necessary to integrate the system modeling tools and simulation tools for analysis. Most of the existing integration methods focus on the integration in the physical architecture phase of the system model. A model integration framework that can integrate simulation into the logical architecture phase of the entire model for synchronous model verification is proposed in this paper. In the integration process, a Model-to-Text method is employed for information extraction and model transformation from the SysML model to the simulation model. The system model can be transformed by reusing and updating the generated simulation model through the framework for model verification. A framework with the Simulink model as the transformation target is constructed as an example in this paper, and the capability of this framework is verified by a design process of a quadruped robot. The result shows that this framework can realize the system design paradigm of integrating system verification for the entire logical architecture, which can improve the design efficiency and provide a reference for other system design and integration work.